How Big a Problem is Too Big to Fail? A Review of Gary Stern and Ron Feldman's Too Big to Fail: The Hazards of Bank Bailouts - Mishkin, Frederic S (Journal of Economic Literature, 2006)
This review essay examines whether too-big-to-fail is as serious a problem as Gary Stern and Ron Feldman contend. This essay argues that Stern and Feldman overstate the importance of the too-big-to-fail problem and do not give enough credit to the FDICIA legislation of 1991 for improving bank regulation and supervision. However, this criticism of the Stern and Feldman book does not detract from many of its messages. The policy recommendations in their book have merit even if the too-big-to-fail problem is currently not that serious because these policies make it less likely that a banking crisis will occur even if driven by other factors.